Overview of Resistive Random Access Memory (RRAM): Materials, Filament Mechanisms, Performance Optimization, and Prospects - Wang, Hong; Yan, Xiaobing (Physica status solidi. PSS-RRL. Rapid research letters, 2019)
Because conventional nonvolatile memory is limited by process technology and physical size, resistive random access memory (RRAM) gradually enters the field of view due to its simple structure, fast program/erase speed, low power consumption, and so on. This review article summarizes the materials, filament mechanisms, performance optimization, and application prospects of RRAM structures to provide readers with a reference for future investigation. The filament mechanisms, which involve the electrochemical metallization mechanism (ECM), valence change mechanism (VCM), and thermochemical mechanism (TCM), of RRAM devices are particularly highlighted. The parameters that determine the RRAM characteristics such as operating voltages, ON/OFF ratio, endurance, and data retention are improved by incorporating the three methods: 1) “interface engineering”, 2) element doping of functional materials, and 3) introduction of low‐dimensional materials. In the last section, a brief introduction to the future RRAM application prospects and challenges is provided. To manufacture reliable resistive random access memory (RRAM) devices that meet the application requirements, an excellent device performance is necessary. This review article summarizes the classification of the functional layer materials, filament mechanisms, mainstream approach of RRAM performance optimization, application prospects, and current challenges of RRAM structures to provide some reference for developing best‐performance devices in the future.